Phytoplankton bloom distribution and succession driven by sea-ice melt in the Kong Håkon VII Hav - Lenss, Megan; Moreau, Sebastien; Hattermann, Tore; Wiktor, Jozef; Różańska, Magdalena; Claeys, Philippe; Brion, Natacha; Chierici, Melissa; Fransson, Agneta; Campbell, Karley (Elementa: Science of the Anthropocene, 2024)
The existence of ice-edge phytoplankton blooms in the Southern Ocean is well described, yet direct observations of the mechanisms of phytoplankton bloom development following seasonal sea-ice melt remain scarce. This study constrains such responses using biological and biogeochemical datasets collected along a coastal-to-offshore transect that bisects the receding sea-ice zone in the Kong Håkon VII Hav (off the coast of Dronning Maud Land). We documented that the biogeochemical growing conditions for phytoplankton vary on a latitudinal gradient of sea-ice concentration, where increased sea-ice melting creates optimal conditions for growth with increased light availability and potentially increased iron supply. The zones of the study area with the least ice cover were associated with diatom dominance, the greatest chlorophyll a concentrations, net community production, and dissolved inorganic carbon drawdown, as well as lower sea surface fugacity of CO2. Together, these associations imply higher potential for an oceanic CO2 sink due, at least in part, to more advanced bloom phase and/or larger bloom magnitude stemming from a relatively longer period of light exposure, as compared to the more ice-covered zones in the study area. From stable oxygen isotope fractions, sea-ice meltwater fractions were highest in the open ocean zone and meteoric meltwater fractions were highest in the coastal and polynya zones, suggesting that potential iron sources may also change on a latitudinal gradient across the study area. Variable phytoplankton community compositions were related to changing sea-ice concentrations, with a typical species succession from sympagic flagellate species (Pyramimonas sp. and Phaeocystis antarctica) to pelagic diatoms (e.g., Dactyliosolen tenuijunctus) observed across the study area. These results fill a spatiotemporal gap in the Southern Ocean, as sea-ice melting plays a larger role in governing phytoplankton bloom dynamics in the future Southern Ocean due to changing sea-ice conditions caused by anthropogenic global warming.
Article Number: 00122
Keywords: Sørishavet; biogeokjemi; fytoplankton; havis; oseanografi; sjøis

Antarctic Blue Ice Areas are hydrologically active, nutrient rich and contain microbially diverse cryoconite holes - Nowak, Aga; Isaksson, Elisabeth; Sunde, Øyvind; Elvevold, Synnøve; Sandven, Håkon; Moholdt, Geir; Hudson, Stephen R.; Urset, Anne; Edwards, Arwyn; Rassner, Sara M. E.; Pearce, David; Hamre, Børge; et al. (Communications Earth & Environment, 2024)
Antarctica is the coldest, windiest and least inhabited place on Earth. One of its most enigmatic regions is scoured by katabatic winds blue ice that covers 235,000 km2 of the Antarctic fringe. Here, we demonstrate that contrary to common belief, high-altitude inland blue ice areas are not dry, nor barren. Instead, they promote sub-surface melting that enables them to become “powerplants” for water, nutrients, carbon and major ions production. Mapping cryoconite holes at an unprecedented scale of 62 km2 also revealed a regionally significant resource of dissolved nitrogen, phosphorus (420 kg km−2), dissolved carbon (1323 kg km−2), and major ions (6672 kg km−2). We discovered that unlike on glaciers, creation of cryoconite holes and their chemical signature on the ice sheet is governed by ice movement and bedrock geology. Blue ice areas are near-surface hotspots of microbial life within cryoconite holes. Bacterial communities they support are unexpectedly diverse. We also show that near-surface aquifers can exist in blue ice outside cryoconite holes. Identifying blue ice areas as active ice sheet ecosystems will help us understand the role ice sheets play in Antarctic carbon cycle, development of near-surface drainage system, and will expand our perception of the limits of life.
Keywords: Antarktis; biogeokjemi; geografi; geologi; mikrobielle organismer; mikrobiologi

Gross Primary Production of Antarctic Landfast Sea Ice: A Model-Based Estimate - Wongpan, Pat; Meiners, K. M.; Vancoppenolle, M.; Fraser, A. D.; Moreau, Sebastien; Saenz, B. T.; Swadling, K. M.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2024)
Much of the Antarctic coast is covered by seasonal landfast sea ice (fast ice), which serves as an important habitat for ice algae. Fast-ice algae provide a key early season food source for pelagic and benthic food webs, and contribute to biogeochemical cycling in Antarctic coastal ecosystems. Summertime fast ice is undergoing a decline, leading to more seasonal fast ice with unknown impacts on interconnected Earth system processes. Our understanding of the spatiotemporal variability of Antarctic fast ice, and its impact on polar ecosystems is currently limited. Evaluating the overall productivity of fast-ice algae has historically been hampered by limitations in observations and models. By linking new fast-ice extent maps with a one-dimensional sea-ice biogeochemical model, we provide the first estimate of the spatio-seasonal variability of Antarctic fast-ice algal gross primary production (GPP) and its annual primary production on a circum-Antarctic scale. Experiments conducted for the 2005?2006 season provide a mean fast ice-algal production estimate of 2.8 Tg C/y. This estimate represents about 12% of overall Southern Ocean sea-ice algae production (estimated in a previous study), with the mean fast-ice algal production per area being 3.3 times higher than that of pack ice. Our Antarctic fast-ice GPP estimates are probably underestimated in the Ross Sea and Weddell Sea sectors because the sub-ice platelet layer habitats and their high biomass are not considered.
Publisher: John Wiley & Sons, Ltd Article Number: e2024JC021348
Keywords: Sørishavet; alger; biogeokjemi; geofysikk; havis; oseanografi; sjøis